APPLICATION OF FRACTION BLOCK MEDIA BASED ON DEEP LEARNING TO IMPROVE STUDENTS' UNDERSTANDING OF FRACTION - Budi Halomoan Siregar; Adi Sinaga; Juanda Rifki Simanjuntak; Qamaruddin Fadhilah Harahap; Rani Nuldiva Situmorang (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This study aims to determine the effectiveness of applying fraction blocks based on a deep learning approach in improving students' understanding of fraction material in the seventh grade of MTs. The type of research used is an experiment with a One Group Pretest-Posttest design. The research subjects were 24 seventh-grade students at MTs Cerdas Murni. Data were obtained through pretest and posttest tests and observation of student learning activities, then analyzed descriptively and inferentially using the t-test. The results show that the average pretest score of students was 63.33, which increased to 72.5 on the posttest, and the t-test results show a significant difference between the two scores (tvalue = 3.406 > ttable = 2.069). These findings prove that the use of fraction block media based on the deep learning approach is effective in helping students understand the conversion of common fractions to mixed fractions and vice versa. In addition, this media is also able to increase student learning activity through more concrete manipulative and visual activities. ABSTRAK Penelitian ini bertujuan untuk menentukan efektivitas penerapan blok pecahan berdasarkan pendekatan pembelajaran mendalam dalam meningkatkan pemahaman siswa tentang materi pecahan pada kelas VII MTs. Jenis penelitian yang digunakan adalah eksperimen dengan desain One Group Pretest-Posttest. Subjek penelitian adalah 24 siswa kelas VII di MTs Cerdas Murni. Data diperoleh melalui tes pretest dan posttest serta pengamatan aktivitas belajar siswa, kemudian dianalisis secara deskriptif dan inferensial menggunakan uji-t. Hasil menunjukkan bahwa rata-rata skor pretest siswa adalah 63,33, yang meningkat menjadi 72,5 pada posttest, dan hasil uji t menunjukkan perbedaan yang signifikan antara kedua skor tersebut (thitung = 3,406 > ttabel = 2,069). Temuan ini membuktikan bahwa penggunaan media blok pecahan berdasarkan pendekatan pembelajaran mendalam efektif dalam membantu siswa memahami konversi pecahan biasa menjadi pecahan campuran dan sebaliknya. Selain itu, media ini juga mampu meningkatkan aktivitas belajar siswa melalui aktivitas manipulatif dan visual yang lebih konkret.